Pengaruh Pengetahuan Kewirausahaan Dan Kepercayaan Diri Terhadap Kesiapan Berwirausaha Mahasiswa Program Studi Pendidikan Ekonomi Angkatan 2020 Universitas Jambi - Rahmadani, Tasya; Arpizal, Arpizal; Sari, Nurmala (Jurusan Pendidikan IPS FKIP UNJA, 2023)
The purpose of this study was to determine the effect of entrepreneurial knowledge and self-confidence on the entrepreneurial readiness of students of the Economics Education Study Program Batch of 2020, University of Jambi. This study uses a quantitative research method Ex Post Facto method. The population of this study consisted of 71 respondents who had attended entrepreneurship courses. The data collection method used by researchers is a questionnaire. The research data was obtained by distributing questionnaires to 2020 Anglatan Economics Education Students at the University of Jambi via a google form. After the questionnaires were distributed, the data were analyzed quantitatively using the SPSS 22.0 application and Ms. Excel. The results showed that partially entrepreneurial knowledge had a significant effect on entrepreneurial readiness as indicated by the value obtained 6.832 > 1.668, with a significance value of 0.000 <0.05. Furthermore, self confidence partially has a significant effect on entrepreneurial readiness as indicated by the value obtained 7.518 > 1.668 with a significance value of 0.000 < 0.05. And simultaneously it also has an effect where the value of is greater than > namely 33.269 > 3.13 and a significance value <0.05 which is 0.000 < 0.05. Then Ha is accepted and H0 is rejected, so that there is a significant influence between Entrepreneurial Knowledge and Self Confidence on Entrepreneurial Readiness of Students of the Economics Education Study Program Class of 2020, University of Jambi.